Talent drain or talent exchange? International recruitment strategies and players characteristics in Italian male youth football - Morganti, G.; Brustio, P. R.; Grossi, A.; Ruscello, B.; Strassoldo di Villanova, F.; Vitarelli, M.; Padua, E.; Kelly, A. L. (Soccer & Society, 2026)
In football, the increasing professionalization, competition, and internationalization in talent identification call for further studies on player migration. This research collected freely accessible online data to examine the geographical subregion of birth (GSB) of foreign youth players who competed in the U19 national league from 2018-19 to 2021-22 and Italian and foreign youth players` roles during the same seasons. Part 1 recorded 541 (30.02%) foreign youth players and an increasing trend in their recruitment over seasons (?2 = 3.87, p = 0.04). Part 2 indicated Italians were more likely to be recruited as goalkeepers and defenders, while foreigners as forwards (?2 = 31.9, p < 0.001) and revealed an association between foreigners` GSB and their role (?2 = 54.9, p < 0.001). Findings highlighted the complex interplay between geohistorical and cultural factors and current talent identification shaping youth football migration. They also underlined the lack of Italian youth forwards that may derive from the defensive playing style traditionally promoted by Italian football.